A case report of gastroschisis: prenatal diagnosis in primary care settings matters - Said, Abdul Hadi; Md Nor, Mohd Zamir; Che Yusof, Mohd Daud (Academy of Family Physicians of Malaysia (AFPM), 2023)
Gastroschisis may lead to serious congenital disability, as prolonged exposure to the amniotic fluid could compromise the mesenteric blood flow and irritate the foetal intestinal wall. The consequences of gastroschisis include spontaneous preterm birth, growth restriction and foetal demise. Awareness of this disease is essential, as a high mortality rate is linked to inadequate initial therapy. Early detection of the disease, mainly by primary care physicians as the initial point of contact, is crucial to improve the course of the condition through early monitoring and referral to tertiary care centres. With this case report, we hope to highlight the need of detecting gastroschisis before to the third trimester of pregnancy for better readiness, especially in primary care settings located far from tertiary centres.